Towards a comparative study of application performance in an automotive environment with 5G non-terrestrial networks - Martino, Luigi; Deutschmann, Jörg; Hielscher, Kai-Steffen; German, Reinhard (IET, 2024)
Non-Terrestrial Networks (NTNs), and in particular satellite networks, are emerging as a promising solution to extend the coverage and capacity of wireless networks beyond the limitations of terrestrial infrastructure. One such technology that has been heavily researched in recent years is 5G, which promises to improve the way we communicate by providing high data rates, machine-to-machine communications and ultra-reliable low-latency communications. In particular, the automotive industry is expected to greatly benefit from 5G, as it can enable a range of advanced applications such as autonomous driving, vehicle-to-vehicle (V2V) and vehicle- to-infrastructure (V2I) communications. However, the deployment of 5G in vehicular environments is still facing significant challenges, such as ensuring reliable and secure communication, providing efficient mobility management, and optimizing the use of radio resources. In this context, this paper provides an overview of automotive applications such as Voice over IP (VoIP), Vehicle Monitoring (based on UDP) and a file bulk transfer (based on TCP) over a Geostationary and Low Earth Orbit link, highlighting the key issues and potential solutions to enable the seamless integration of vehicular communications into these emerging network